Hospital preparedness for disasters: a global perspective on research trends in health promotion and resilience - Arini, Merita; Iring Primastuti, Harumi; Pribadi, Firman; Nuryakin; Anggara, Cornel; Listiowati , Ekorini; Agus Samsudin, Mohammad (Universitas Ahmad Dahlan, 2026)
Hospitals play a central role in maintaining the continuity of healthcare services during crises, underscoring the strategic necessity of disaster preparedness to strengthen the health system’s resilience. This study analyzed global trends, research developments, and scientific influences related to hospital disaster preparedness to identify knowledge gaps and future priorities for enhancing resilience and promoting health. Data were retrieved from the Scopus database using the keywords “hospital” and “disaster preparedness” for the years 2015–2025, screened according to the inclusion criteria, and analyzed using VOSviewer and Scopus Analytics. A total of 628 articles met the criteria. The number of publications increased sharply after 2020, with notable dominance by high-income countries and leading academic institutions with substantial research funding. Bibliometric mapping revealed four major research clusters: (1) hospital emergency management and system preparedness, (2) healthcare workforce resilience and lessons from the pandemic, (3) education, training, and behavioral preparedness, and (4) cross-country collaboration in disaster response. Although the multidisciplinary dimension of hospital preparedness is evident through the inclusion of engineering and computer science fields, technology-related keywords did not appear at the applied threshold, suggesting that research on technology integration remains limited. Contributions from Low- and Middle-Income Countries (LMICs) are also underrepresented, highlighting disparities in research capacity and funding. This study expands global understanding of hospital disaster preparedness by identifying emerging and underexplored areas, emphasizing the importance of multidisciplinary collaboration, equitable research partnerships, and the integration of health promotion approaches to build adaptive, resilient hospitals worldwide.